Donato Menichella: dal risanamento di banche e industrie allo sviluppo del Mezzogiorno - Mario Sarcinelli (Moneta e Credito, 2013)
Donato Menichella was the central-bank governor when Italy's reconstruction and economic miracle took place. While well known are the merits he acquired in the '50s, less understood is the role he played to resolve the nexus between banks and industrial concerns in the '20s and above all in the '30s, when he was called upon to organise IRI, the Institute for Industrial Reconstruction conceived by Beneduce, and to write, together with others, the fundamental banking law of 1936. As a governor native of the South, he was well aware of Mezzogiorno's backward conditions. His was the idea as well as the bill that eventually set up Cassa del Mezzogiorno, the Development Fund for the South. Menichella was a great manager and a grand commis with a high sense of equity and a strong aversion to the limelight, either academic or political.